Typification of Angiospermae described from the Bonin Islands 1: Metachlamydeae - Watanabe-Toma, Kana; Ohi-Toma, Tetsuo; Murata, Jin (Phytotaxa, 2011)
During the preparation of a database of plant specimens from the Bonin Islands, Japan, we found several cases in which type material for taxa described from the islands was uncertain. This is either because specimens were not cited, because cited specimens in protologues include multiple collections, or because the citations contained ambiguous locality and/or collector data. Thus, many Bonin Islands species require typification. Here, lectotypes are newly designated or reconfirmed for 10 taxa, based on the herbarium materials of Metachlamydeae at the Botanical Gardens section of TI Herbarium, the University of Tokyo.